Modelagem e simulação de processos (corte, carregamento e transporte) na produção agrícola de açúcar e álcool - Silva, Ana Thereza Barbosa da (2012)
This paper aims to simulate and analyze the steps of cutting, loading and transportation of sugar cane for production planning in the sugar and alcohol industry. Agricultural steps are responsible for about 30% of the production full cost. In the simulations, there was applied the arc routing procedure from the TransCAD software. This software works with a traffic network based on concepts arising from the Graph Theory, approached in this study. Starting from the premise that sugar cane has rapid deterioration after harvest and which therefore needs to be delivered within 72 hours industrialization, agricultural management is expected to develop a detailed logistical planning to avoid the involvement of industrial efficiency. It was considered in this study, factors such as the geometry and size of plots, the points of maneuver and load transfer and operating cycles. Therefore, it was possible by the usage of TransCAD software, to generate optimized harvest areas, which could allow the operations, improve the processes, reduce the losses, promote directed actions to facilitate operations with machinery and lower the operational costs. The software proved to be a tool for supporting decisions involved in planning and controlling the production of a sugar and alcohol, both in agricultural operations and the logistics of moving machinery in the field. Thus it was useful to promote the maximization of productivity. Even with some limitations, the software has helped in achieving the results came up the initial goals proposed.